2020
DOI: 10.1001/jamanetworkopen.2020.4049
|View full text |Cite
|
Sign up to set email alerts
|

Association of Long-term Strenuous Physical Activity and Extensive Sitting With Incident Radiographic Knee Osteoarthritis

Abstract: IMPORTANCE Persons with knee symptoms recognize the health benefits of engaging in physical activity, but uncertainty persists about whether regular strenuous physical activity or exercise can accelerate tissue damage. A sedentary lifestyle of inactivity or underloading may also be associated with deleterious joint health. OBJECTIVE To establish whether long-term strenuous physical activity participation and extensive sitting behavior are each associated with increased risk of developing radiographic knee oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The lowest scores in these categories were 0.41 for Aweto et al [ 58 ], a cross-sectional study in the general population category; 0.36 for Omokhodion et al [ 94 ], a cross-sectional study in the observational-occupational category; and 0.42 for Engelen et al [ 122 ], a non-RT without control design pilot study in the experimental/intervention category. The highest score among the general population category was 0.95 scored in six studies [ 16 , 64 , 66 , 67 , 75 , 76 ]. In the occupational category, the highest score in observational studies was 0.95 scored by six studies [ 39 , 57 , 100 , 109 , 114 , 129 ], and in experimental/intervention studies was 0.96 for one study, Brakenridge et al [ 121 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest scores in these categories were 0.41 for Aweto et al [ 58 ], a cross-sectional study in the general population category; 0.36 for Omokhodion et al [ 94 ], a cross-sectional study in the observational-occupational category; and 0.42 for Engelen et al [ 122 ], a non-RT without control design pilot study in the experimental/intervention category. The highest score among the general population category was 0.95 scored in six studies [ 16 , 64 , 66 , 67 , 75 , 76 ]. In the occupational category, the highest score in observational studies was 0.95 scored by six studies [ 39 , 57 , 100 , 109 , 114 , 129 ], and in experimental/intervention studies was 0.96 for one study, Brakenridge et al [ 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four high-quality cross-sectional studies, three of adults ≥ 45 years in the general population cohorts [ 16 , 59 , 60 ] and one study of adults < 40 years in the occupational cohorts [ 105 ] reported a positive association of full-day SB with knee pain (osteoarthritis), including one study that reported the association only in men [ 59 ]. There was one prospective study [ 76 ] that reported no association of extensive full-day SB with knee pain. According to the best-evidence synthesis, we concluded there is strong evidence of cross-sectional association of full-day SB with knee pain in middle-aged to older adults, however, there is insufficient evidence whether the association is gender-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…As is common in the literature, when an individual scores above that cut-off, this individual was considered to have clinically relevant symptoms of a MH disorder. We also included 2 studies [ 38 , 53 ] that, even though they used a validated MH scale, did not use a specific cut-off but rather performed analysis by categories of severity of symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Although moderate physical activity is encouraged to improve one's general health, repetition or incorrect execution of movements is the prevailing cause of OA in both young and older adults ( 56 , 64 , 107 ). From a comprehensive review of recent studies, common occupational activities such as sitting (hip and knee OA), lifting (knee OA), driving (knee OA), and squat (lower limb OA) have been associated with increased risk of OA ( 108 , 109 ).…”
Section: Applications Of Msc Therapies In Oamentioning
confidence: 99%